Traduire ce que les mots ne disent pas, mais ce qu'ils font - Meschonnic, Henri (Meta, 1995)
AbstractContinuing his reflection and work on rhythm, the author shows how a poetics of translation can overcome the limits of a theory of sign based on the meaning/form dichotomy. As an alternative to this approach, which situates the poem and the translation in a logic of discontinuity, the author proposes that language and translation he reconsidered from the viewpoint of the continuity of discourse and the unity of rhythm. Consequently, translation consists in translating not what words say, hut what they do. As an example, the author applies this approach to the translation of the famous first two verses of Psalm 22.